Students’ Perceptions towards the Use of E-Learning UNP during Covid-19 Pandemic : A Case Study of English Department Students at Universitas Negeri Padang - Reska Lismardayani; Witri Oktavia (Journal of English Language Teaching, 2021)
The spread of the COVID-19 pandemic in Indonesia is causing some changes in various sectors, such as education in Indonesia. All schools are required to carry out online learning. Along with online learning practices, teachers use online learning to support the teaching and learning process, such as providing learning materials and delivering learning materials by utilizing technology. This study aims to explore students' perception of English learning materials during online learning using UNP e-learning. The samples in this study were taken randomly and selected one grade K4 2019 with a total of 29 students. They were asked 27 questions to explore their perceptions of UNP's e-learning use during online learning. Descriptive quantitative was used in this study. In general, almost all students feel that the use of UNP e-learning can contribute positively to their learning. The results showed that UNP e-learning is easy to use (M = 4.41) and UNP's E-learning contributes positively to students' learning experience (M = 4.14) as the most important characteristics of effective use of UNP e-learning. Overall, stakeholder perceptions are in a good category. Although there were still some students who complained about some problems through the use of e-learning UNP.